Modeling and simulation of logistics flows. 3, - Reveillac, Jean-Michel (ISTE, Ltd. ; Wiley, 2017)
Volume 3 begins with an introduction to which are added four chapters focused on modeling and flow simulation in an environment in 2 or 3 dimensions (2D or 3D). They deal with different cases taken from situations found in the field. A conclusion comes close this third book: - The different software used in this third volume; - Computer simulation of discrete flows; - Mixed flow simulation; - Flows in 3D and the evacuation simulation; - Flows in 3D for conveying and storage The conclusion discusses the future developments of the software and their integration into society. At the end of each volume is a bibliography and a list of web links. There is also a glossary explaining some abbreviations, acronyms and some very specific terminology of logistics and operations research.- Resumé vydavatel